2012
DOI: 10.1016/j.socscimed.2011.08.038
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the efficacy of HIV/AIDS prevention interventions in Asia, 1995–2009

Abstract: The HIV/AIDS epidemic continues to grow in pockets across Asia, despite early successes at curtailing its spread in countries like Thailand. Recent evidence documents dramatic increases in incidence among risk groups and, alarmingly, the general population. This meta-analysis summarizes the sexual risk-reduction interventions for the prevention of HIV-infection that have been evaluated in Asia. Sexual risk-reduction outcomes (condom use, number of sexual partners, incident sexually transmitted infections [STI]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 72 publications
4
24
0
Order By: Relevance
“…The results of this meta-analysis are consistent with prior studies indicating that interventions achieve better risk-reduction results when they take place in countries with a lower HDI index; interventions appear to work best where need is greatest,50 51 at least on relatively short-term assessments. Interventions with more intervention content, as measured by the number of intervention sessions, also trended toward greater efficacy in increasing condom use 52.…”
Section: Discussionsupporting
confidence: 86%
“…The results of this meta-analysis are consistent with prior studies indicating that interventions achieve better risk-reduction results when they take place in countries with a lower HDI index; interventions appear to work best where need is greatest,50 51 at least on relatively short-term assessments. Interventions with more intervention content, as measured by the number of intervention sessions, also trended toward greater efficacy in increasing condom use 52.…”
Section: Discussionsupporting
confidence: 86%
“…A recent meta-analysis of behavioral interventions conducted in various settings and multiple countries found intervention effects for increased condom use and reduced STI/HIV incidence (3). Similar results appeared in meta-analyses of multi-session risk reduction interventions conducted with adolescents(4), men and women in Latin American and Caribbean countries(5), and in Asia (6). Despite these successes, sexual risk reduction interventions are typically presented in multiple sessions, and as a result may create issues with participant retention over time.…”
Section: Introductionsupporting
confidence: 71%
“…In delivering behavioural HIV interventions, community mobilisation strategies may provide the most promising opportunity to increase large-scale uptake of HIV prevention strategies (Sweat et al 2011; Tan et al 2012; Townsend, Mathews, and Zembe 2013). Prior studies demonstrated that the uptake of HTC can be enhanced in communities with diverse cultures and infrastructures (Sweat et al 2011).…”
Section: Behavioural Interventionsmentioning
confidence: 99%